Biological therapies in Crohn's disease: are they cost-effective? A critical appraisal of model-based analyses. (December 2014) - Marchetti, Monia; Liberato, Nicola Lucio
<x xml:space="preserve">Abstract</x> In refractory Crohn's disease, anti-TNF and anti-α 4 integrin agents are used for ameliorating disease activity but impose high costs to health-care systems. The authors systematically reviewed cost–effectiveness analyses based on decision models: most of the studies were judged to have a good quality, but a large portion assessed health and costs in a short time horizon, usually disregarding fistulizing disease and not considering safety. Infliximab induction followed by on-demand retreatment consistently proved to have a good cost per quality-adjusted life year, while maintenance treatment never satisfied commonly accepted cost-utility thresholds. Challenges in cost–effectiveness analysis include the lack of a standard model structure, a large variability in the costs of surgery and poor data on indirect costs. As clinical practice is moving to mucosal healing as a robust response marker, personalized schedules of anti-TNF therapies might prove cost-effective even in the perspective of the health-care system in the near future.